Capital Market Implications of Corporate Disclosure: German Evidence - Michael Grüning (BuR - Business Research, 2011)
This paper investigates the relationship between annual report disclosure, market liquidity, and capital cost for firms registered on the Deutsche Börse. Disclosure is comprehensively measured using the innovative Artificial Intelligence Measurement of Disclosure (AIMD). Results show that annual report disclosure enhances market liquidity by changing investors expectations and inducing portfolio adjustments. Trading frictions are negatively associated with disclosure. The study provides evidence for a capital-costreduction effect of disclosure based on the analysis of investors return requirements and market values. Altogether, no evidence is found that the information processing at the German capital market is structurally different from other markets.
urn:nbn:de:0009-20-29772
Keywords: 650; annual report disclosure; capital market; cost of capital; market liquidity; Unternehmenspublizität; Finanzmarkt; Liquiditätseffekt; Regression; Börse; Deutschland